Thematic analysis of the policies of Iran's health higher education - Mitra Sarshar; Shahram Yazdani; Mohammad Pooyan Jadidfard; Lida Shams (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: In 1985, the Iranian parliament approved the integration of Medical Education and Health Services and the establishment of the Ministry of Health and Medical Education, which has since been the policymaker of Health Higher Education in Iran. The policies are not based on a codified framework and many were abolished at some point. Some critical issues are not addressed and some activities overlap. The purpose of the present study was to identify the content themes of core policies in the Iranian Health Higher Education system and provide a detailed policy orientation taxonomy. MATERIALS AND METHODS: This qualitative study was conducted in 2019 using the thematic content analysis of documents relevant to Higher Education and Health Higher Education, including upstream documents, and documents and enactments of the Deputy Minister of Education and its policy centers. RESULTS: From 586 policy documents, six main themes or six core policy orientations in the Health Higher Education System were identified, including Development of Medical Education System Policies; Ensuring the Alignment of Operations with Policies; Policies Related to Medical Education Development; Value-orientation; Networking and Development of Medical Education System Interactions; and the Development of Research, Management, and Translation of Medical Education knowledge. CONCLUSION: Developing a taxonomy of Health Higher Education policy orientations helps policymakers identify the neglected and overstressed areas. It can provide education policymakers with categorized and comprehensive information to quickly access accurate information, make informed decisions, avoid mistakes, and increase productivity.